Prevalence of mutilations and other skin wounds in working donkeys in Tamil Nadu, India. (13th October 2018) - Rayner, Emma L; Airikkala‐Otter, Ilona; Susheelan, Aswin; Mellanby, Richard J; Meunier, Natascha V; Gibson, Andrew; Gamble, Luke
Abstract : Wounds in working donkeys are a common and preventable welfare problem in many countries. Mutilations, iatrogenic injuries carried out by owners, are a particularly distressing welfare issue. However, little is known about their nature and prevalence. The project aim was to assess the general health and establish the prevalence, nature and severity of mutilations and other skin wounds in donkeys from several communities in Tamil Nadu, India, that were part of a donkey welfare initiative run by the Worldwide Veterinary Service charity. Five hundred and eighty‐two donkeys were examined from five locations and data collected using a predesigned, smartphone app between October 2016 and July 2017. The study revealed that 298 wounds were present in a total of 227 donkeys (39.0 per cent of the population). Mutilations, comprising nose‐splitting, ear‐splitting and branding, were the most common type of skin wound, comprising 62.8 per cent of all wounds. Poorly fitting harnesses and hobbles were also a common cause of injury. These data can be used to design future‐targeted and focused, educational interventions to reduce mutilation practices which are a common and important welfare issue. Further outreach initiatives are urgently needed to improve welfare of donkeys in these regions.